Intrinsic anomalous Hall conductivity and real space Berry curvature induced topological Hall effect in Ni2MnGa magnetic shape memory alloy - Singh A.K.; Shukla G.K.; Singh S. (My University, 2025)
Anomalous and topological Hall effect (THE) are the fascinating electronic transport properties in condensed matter physics and received tremendous interest in the field of spintronics. Here, we report the intrinsic anomalous Hall conductivity (AHC) and THE in the bulk Ni2MnGa magnetic shape memory alloy. The magnetization measurement reveals the premartensite, martensite and magnetic phase transitions. A detailed analysis of AHC reveals that the intrinsic Berry phase mechanism dominates over skew scattering and side jump in all the structural phases of Ni2MnGa. Further, an additional contribution in the Hall resistivity is observed as THE. The magnitude of the THE and its temperature independent behavior indicates that the THE arises due to the real space Berry curvature induced by topologically protected magnetic skyrmion textures in the martensite and premartensite phases of Ni2MnGa. The larger magnetic field is required to vanish the topological Hall resistivity in the martensite phase in comparison to the premartensite phase, which manifests the more stable skyrmion textures in the martensite phase. The present findings open a new direction in the field of functional materials, which hosts skyrmion, exhibits anomalous transport and magnetic shape memory effect. © 2022 IOP Publishing Ltd.